Potencial utilização de areia de fundição na construção civil: um estudo de caso para a cidade de São Carlos - SP - Carassato, Douglas Trofino (Universidade Federal de São Carlos, 2023)
The general objective of the research was to understand the importance of using foundry sand in civil construction. The specific objectives of this work were: to discuss environmental sustainability; explain the importance of conscious use of natural resources and clean technologies; explain the correct management and reduction of waste; identify the importance of using foundry sand in civil construction. The methodological procedure used in this research is a descriptive qualitative bibliographic review, since it is supported by a theoretical review. Once the research objectives were defined, the collection of information began based on the study of national and international bibliographies. A case study for the JC Metals foundry, in São Carlos, was carried out in order to verify if there is a possibility and feasibility of reusing the sand discarded by the company, based on the results observed in the bibliographic review carried out throughout the text. It was concluded that the reuse of discarded foundry sand showed potential for its use in concrete and other areas, provided that a chemical analysis demonstrated that there would be no environmental risk, so the construction sector could easily absorb this residue. Cost calculations also showed that there could be savings if JC Metals donated its sand to concrete plants located nearby, thus reducing the cost of disposal in landfills. Although many states have developed regulations on reuse for industrial byproducts, large amounts of smelter byproducts are still being landfilled across the planet. However, reuse of foundry products is increasing in a variety of areas, including the highway and construction industries.
Potential use of waste foundry sand in civil construction: a case study for the city of São Carlos - SP
Keywords: Reutilização da areia de fundição; Sustentabilidade; Construção civil; São Carlos-SP; Waste foundry sand reuse; Sustainability; Construction; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS